Factors influencing the teaching of Building Information Modeling (BIM) among civil technology lecturers in vocational colleges in Sabah / Ruzaini Rafiuddin Rasmet, Nur Farha Shaafi and Mohd Hizwan Mohd Hisham - Rasmet, Ruzaini Rafiuddin; Shaafi, Nur Farha; Mohd Hisham, Mohd Hizwan (Universiti Teknologi MARA, Kedah, 2025)
The integration of Building Information Modeling (BIM) into vocational education presents challenges in aligning pedagogy with industry needs. While BIM adoption has increased in Malaysia's construction sector, the readiness of vocational lecturers to teach BIM remains uncertain. This study examines key pedagogical factors influencing BIM instruction in vocational colleges in Sabah, focusing on lecturers' competencies, institutional facilities, and teaching aids. Using a descriptive quantitative approach, the study identifies gaps in BIM-specific training, inadequate facilities, and limited access to interactive teaching resources. Findings suggest that enhanced lecturer competency through targeted professional development, upgraded infrastructure, and improved digital teaching aids are critical for effective BIM instruction. This study contributes to TVET pedagogy by highlighting the need for structured training programs and industry collaboration to ensure that BIM education fosters both technical and creative learning approaches. Strengthening BIM instruction will ultimately improve graduates' employability and adaptability in the evolving construction landscape.